2007
DOI: 10.1039/b614232j
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-conducting oxygen permeable ceramic membranes for the carbon dioxide reforming of methane

Abstract: Due to the high economic, environmental, and safety costs associated with pure oxygen, mixedconducting oxygen-permeable ceramic membranes are being explored as an alternative oxygen source for hydrocarbon conversion reactors. This work reports a dramatic improvement in catalyst performance when an oxygen-permeable SrFeCo 0.5 O x ceramic membrane is used in conjunction with a conventional powder Pt/ZrO 2 catalyst for the CO 2 reforming of CH 4 . Experiments comparing catalyst performance with up to 2% co-fed ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Previous studies of the oxygen assisted carbon dioxide reforming of methane at 800°C have shown that when a disk-shaped SFC ceramic membrane is used in conjunction with an unreduced Pt/ZrO 2 catalyst, the oxygen from the ceramic membrane is more beneficial to the methane conversion than the co-fed oxygen [2]. This increased activity has been ascribed to two factors.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies of the oxygen assisted carbon dioxide reforming of methane at 800°C have shown that when a disk-shaped SFC ceramic membrane is used in conjunction with an unreduced Pt/ZrO 2 catalyst, the oxygen from the ceramic membrane is more beneficial to the methane conversion than the co-fed oxygen [2]. This increased activity has been ascribed to two factors.…”
Section: Introductionmentioning
confidence: 93%
“…H 2 ) from methane using non-porous oxygen-conducting ceramic membranes as an alternative to the conventional expensive process based on an air separation plant [1,2]. The interest in such selective ceramic membranes is due to their intrinsic ability to act as oxygen suppliers or oxygen distributors at high temperatures in the oxidation process of methane [1,3,4] or other hydrocarbons [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It provides a practical and effective way for the utilization of the two major greenhouse gases (CO 2 and methane) [2]. Many catalysts, including Ni-based catalysts and supported noble metal catalysts, show excellent activity for the CO 2 reforming of methane [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) reforming of methane to synthesis gas attracts ever-growing interest from both environmental and industry aspects [1][2][3][4][5][6]. It provides a practical and effective way for the utilization of the two major greenhouse gases (CO 2 and methane) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent research developments show much focus on the design of chemically tolerant membranes. This is proven based on several successful studies on the implementation of integrated catalytic membrane reactor systems for reactions such as CO 2 -mediated reforming of methane (Slade et al, 2007;Yang et al, 2013;Kathiraser et al, 2013b). Substantial work, however, is required to enhance the robustness as well as inherent permeability characteristics of the membrane under the harsh chemical reaction environment.…”
Section: Future Perspectivesmentioning
confidence: 99%